2016
DOI: 10.3390/nu8030109
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of Body Mass Index Effect on in Vitro Fertilization Outcomes

Abstract: The effect of a raised body mass index (BMI) on the outcome of assisted reproduction technology (ART) still represents a controversial issue. Even less clear is whether BMI acts with a potential detrimental effect on IVF outcomes via a deleterious effect on innate quality of oocytes or on the environmental milieu within the uterus. With the aim to better understand the mechanisms underlying the potential deleterious effect of an increased BMI on IVF outcomes, we have evaluated the effects of female BMI on numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 63 publications
7
33
1
4
Order By: Relevance
“…Obesity has been associated with a significantly higher risk of miscarriages (RR, 1.23; 95% CI, 1.20–1.26) . These results are similar to those of other studies and meta‐analyses …”
Section: Discussionsupporting
confidence: 89%
“…Obesity has been associated with a significantly higher risk of miscarriages (RR, 1.23; 95% CI, 1.20–1.26) . These results are similar to those of other studies and meta‐analyses …”
Section: Discussionsupporting
confidence: 89%
“…This nding was consistent with previous studies, which reported that raised BMI has no adverse effect on clinical pregnancy rate and live birth rate 20,[28] . In addition, our nding con rmed the previous investigations of an increased risk of spontaneous abortion in raised BMI women following treatment of ART [31][32][33]. The reasons for an increased risk of abortion among overweight / obese women are still not well understood.…”
Section: Discussionsupporting
confidence: 87%
“…Data on the potential effects of elevated BMI on fertility treatment outcomes are conflicting. Multiple studies have reported no significant adverse effects of elevated BMI on IVF outcomes [28][29][30][31][32]; however, others have found associations between elevated BMI and higher gonadotropin requirements, fewer oocytes collected, higher cancellation rates, reduced pregnancy and live birth rates, and higher miscarriage rates [33][34][35][36][37][38][39][40][41][42][43][44][45]. Whether obesity has a negative effect on implantation and postimplantation events and on oocyte and embryo quality remains uncertain.…”
Section: Discussionmentioning
confidence: 99%